Prevalence of pre-iridal monocellular and fibrovascular membranes in canine globes affected with congenital glaucoma associated with anterior segment dysgenesis, primary glaucoma associated with goniodysgenesis, and secondary glaucoma - Bedos, Leila; Sandmeyer, Lynne; Campbell, John; Grahn, Bruce H. (Frontiers in Veterinary Science, 2024)
Objectives: (i) to evaluate the prevalence of pre-iridal monocellular and fibrovascular membranes in canine globes affected with congenital glaucoma associated with anterior segment dysgenesis (ASD), primary glaucoma associated with goniodysgenesis (GD), and secondary glaucoma, (ii) examine the associations of these membranes by breed, gender, age and histopathologic ocular changes. Methods: Records of dogs who had eyes enucleated due to blindness and uncontrolled glaucoma were reviewed. Glaucoma was categorized clinically and histologically into three groups: congenital/ASD, primary/GD, and secondary glaucoma.The presence or absence and type of pre-iridal membrane (monocellular or fibrovascular) and other intraocular histologic findings were reviewed and compared statistically for each group.Results:108 canine globes (101 dogs) were included. Pre-iridal monocellular membranes were identified with light microscopy in 10/19 congenital/ASD, 29/40 primary, and 23/49 secondary glaucoma globes. Fibrovascular membranes were seen in 3/19 congenital/ASD, 9/40 in primary, and 24/49 secondary glaucoma globes. There were no associations between type of membrane and breed, gender or age. Peripheral anterior synechiae were more common in globes with fibrovascular membranes and uveal atrophy was more common in globes with monocellular membranes. Conclusion: Pre-iridal monocellular membranes are common in all types of canine glaucoma. They are seen with light microscopy most easily in cases of primary glaucoma, and they are masked by pre-iridal fibrovascular membranes in other forms of glaucoma.